Referral Pattern of 99mTechnetium Thyroid Scan Patients with Suspected Subacute Thyroiditis Before and After the Covid-19 Period - Sarkar, Shimul; Bailey, Shamsun Nahar; Ferdous, Jasmin; Sajjad Al Mishal, Mohammad; Begum, Fatima (Bangladesh Journal of Nuclear Medicine, 2024)
Subacute thyroiditis (SAT) is a transient inflammatory condition of the thyroid gland, often triggered by viral infections or drug exposure, predominantly affecting females between the ages of 20 and 40. This study is aimed at observing the association between COVID-19, vaccination, and patients presenting symptoms suggestive of SAT using 99mTc-Thyroid scans. A total of 1,935 patients with suspected subacute thyroiditis from 2017 to 2022 were retrospectively assessed based on clinical history, blood parameters, high resolution ultrasound (HRUS) of neck, 131I thyroid uptake, and 99mTc scans. They were classified into three groups: Group I : pre-COVID-19 (2017.2018), Group II: during COVID-19 (2019.2020), and Group III: post-COVID-19 (2021.2022). The hallmark of diagnosing SAT in a sonographically intact thyroid gland is absence of radiotracer concentration in a 99m Tc thyroid scintigraphy. In Group-I, 6.6% (493 out of 7,359), Group-II, 11.34% (568 out of 5,007), and Group-III, 14.23% (874 out of 6,138), patients were reported as SAT. Male to female ratio was 1:1.6 (Group I), 2:1(Group II), and 1.2:1 (Group III), respectively. Other parameters, such as thyroid uptake at 24 hours, were less than 4%, serum TSH levels were low, and FT3 and FT4 levels were in the upper limit of the normal range. The number of suggestive SATs was noticed more in the post-COVID period and after vaccination than in the non-COVID period. Bangladesh J. Nuclear Med. 26(2): 155-159, 2023